Characterization of volatile organic compound emissions from consumer level material extrusion 3D printers. (August 2019) - Davis, Aika Y.; Zhang, Qian; Wong, Jenny P.S.; Weber, Rodney J.; Black, Marilyn S.
Abstract: Fused filament fabrication (FFF) printers, the most common type of office, educational, and consumer-level 3D printers, emit complex mixture of volatile gases and ultrafine particles (UFPs) that can deteriorate indoor air quality (IAQ). It is important to understand their potential health risks as the technology becomes more prevalent. The developed method for characterizing and quantifying emissions from an operating FFF 3D printer measures particulate and volatile organic compound (VOC) concentrations over time using an environment controlled testing chamber. Characterization of 3D printer emissions is critical for understanding the chemical safety of this technology for providing guidance to minimize exposure to unintentional hazardous emissions. This study found 3D printers to be a source of numerous VOCs and particles that can be released into the indoor air with 216 individual VOCs identified. These VOCs were assessed for their indoor air and human exposure impact. The specific VOCs released during printing varied depending on the filament material. Filament monomers and degradation byproducts were identified in air samples. Total VOC emissions ranged from 147 μg h −1 for polyvinyl alcohol filament to 1660 μg h −1 for nylon filament. Nozzle temperature, filament material, filament brand, printer brand, and filament color all affected VOC and particle emissions. Personal exposure levels and room exposure levels in two indoor situations, a bedroom and a classroom, were predicted for certain VOCs known or suspected to be carcinogens or irritants. Some chemicals of concern exceeded recommended indoor levels linked to adverse health effects. Exposure levels could be minimized by operating verified low-emitting 3D printers and filaments, reducing the printer nozzle temperature when possible, increasing ventilation around the printer, and providing local exhaust. Highlights: 3D printing is a source of numerous VOCs, 216 chemicals detected. Many VOCs detected are irritants with carcinogenic/reproductive toxicity potentials. Emissions can be affected by 3D printing conditions and filament parameters. Test and measurement methods impact predicted exposure concentration. Predicted concentrations suggest users minimize direct exposure to 3D printing.